A report to inform the development of a clinical practice guideline for rehabilitation post total knee arthroplasty in a South African public hospital - Wood, Wendy-Ann (My University, 2011)
There is no published research available that evaluates the outcome of TKA in South African public hospitals. Prior to this project, there was no South African published research on the role of physiotherapy in patients post TKA. There are also no clinical practice guidelines in South Africa for rehabilitation post TKA. International guidelines may not be appropriate within a South African public hospital context. One of the issues raised in the literature pertaining to CPG development is that they lack practical detail and clarity of how decisions are made. In the current context, these problems may be compounded due to the lack of published research in the field in South Africa. The report that is presented is an attempt to combat these issues when a CPG for physiotherapy post TKA in a South African public hospital is developed. The aim of this study was to draft a report that could inform a comprehensive physiotherapy intervention (in the form of a clinical practice guideline) for patients undergoing a TKA in a tertiary care public hospital in urban South Africa. This was achieved through a series of four studies. The first study involved translating and establishing reliability of the Oxford Knee Score. The second study was a survey of current physiotherapy practice in the management of patients post TKA in South Africa. The third study was a prospective cohort study to establish the effect of an in-patient treatment protocol for use in the final study. The final study was an observational study to explore the outcome of patients post TKA and identify those who may be at risk for poor outcome. The English and translated versions of the Oxford Knee Score was shown to be reliable in this sample. This provided an outcome measure that can be used in the validation and evaluation phases of CPG development. The survey of current practice highlighted the high rate of staff turnover and the relative inexperience of physiotherapists working with patients post TKA in the public sector. It identifies the junior physiotherapists as potential stakeholders in the CPG. The trial of the in-patient physiotherapy protocol rendered similar findings to other similar studies in that a specific physiotherapy intervention did not have any effect on short term outcomes. It puts forward clear clinical questions to facilitate the development of the CPG, particularly relating to scheduling and delivery of weekend and out-patient therapy. The final study provided a demographic profile of the patients within the study context, who are potential stakeholders in the CPG development process. In addition it revealed that level of education, the presence of a caregiver at home, marital status and lack of previous exposure to physiotherapy form part of the profile of an ‘at risk’ patient. When the contribution that this thesis has made thus far to the CPG development process, is appraised using the AGREE tool, it shows that the thesis has contributed to 11 out of 23 of the criteria on the AGREE tool. It has therefore resulted in a report that informs the development of a clinical practice guideline for the physiotherapy management of patients post total knee arthroplasty in a tertiary care public hospital in Gauteng, South Africa.
Keywords: rehabilitation; Knee Arthroplasty; Rehabilitation